2022
DOI: 10.3390/cells11030355
|View full text |Cite
|
Sign up to set email alerts
|

Neuron–Microglia Contact-Dependent Mechanisms Attenuate Methamphetamine-Induced Microglia Reactivity and Enhance Neuronal Plasticity

Abstract: Exposure to methamphetamine (Meth) has been classically associated with damage to neuronal terminals. However, it is now becoming clear that addiction may also result from the interplay between glial cells and neurons. Recently, we demonstrated that binge Meth administration promotes microgliosis and microglia pro-inflammation via astrocytic glutamate release in a TNF/IP3R2-Ca2+-dependent manner. Here, we investigated the contribution of neuronal cells to this process. As the crosstalk between microglia and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It has been shown that METH induces different inflammatory mediators via activation of the NF-κB and other pathways in N9 and BV2 microglial cell lines [ 136 - 138 ]. On the other hand, Canedo et al (2016), Frank et al (2021) and Bravo et al (2022) have showed that METH can not directly activate microglial cells in primary cell culture models [ 37 , 150 , 238 ]. Instead, glutamate and TNF-α released by astrocytes mediated METH-induced microglial activation.…”
Section: Responses Of Microglia To Psychostimulantsmentioning
confidence: 99%
“…It has been shown that METH induces different inflammatory mediators via activation of the NF-κB and other pathways in N9 and BV2 microglial cell lines [ 136 - 138 ]. On the other hand, Canedo et al (2016), Frank et al (2021) and Bravo et al (2022) have showed that METH can not directly activate microglial cells in primary cell culture models [ 37 , 150 , 238 ]. Instead, glutamate and TNF-α released by astrocytes mediated METH-induced microglial activation.…”
Section: Responses Of Microglia To Psychostimulantsmentioning
confidence: 99%
“…Bravo et al first verified on a microfluidic device that there is no contact/a noncontact-dependent mechanism for signal communication between hippocampal neurons and microglia exposed to methamphetamine stimulation. [135] Ndyabawe et al developed a BoC with a neural network representing multiple brain regions. Human neural stem cells were placed in different culture cells of perfusion-free microdevices and injected into dopaminergic neurons and GABA neurons, limiting the spread of chemical agents between cell cultures.…”
Section: Addictionmentioning
confidence: 99%
“…first verified on a microfluidic device that there is no contact/a noncontact‐dependent mechanism for signal communication between hippocampal neurons and microglia exposed to methamphetamine stimulation. [ 135 ] Ndyabawe et al. developed a BoC with a neural network representing multiple brain regions.…”
Section: Application Of Bocsmentioning
confidence: 99%
“…Microglia are the resident macrophages of the brain, accounting for 5–10% of all cells in the central nervous system ( Pelvig et al, 2008 ; Mondelli et al, 2017 ). In the healthy CNS, microglia are habitually present in a dormant state with ramified morphology, but nonetheless release neurotrophic factors that contribute to the regulation of synaptic homeostasis, especially in the contexts of neurotoxic or traumatic brain injury ( Rodríguez-Gómez et al, 2020 ; Bravo et al, 2022 ). Indeed, a diverse range of factors can provoke microglial activation and changes in morphological phenotype ( Wolf et al, 2017 ), for example in response to a high dietary intake of sucrose ( Patkar et al, 2021 ), which is a characteristic of modern western diets.…”
Section: Introductionmentioning
confidence: 99%